1999
DOI: 10.1557/s1092578300002660
|View full text |Cite
|
Sign up to set email alerts
|

Structure of AlN on Si (111) Deposited with Metal Organic Vapor Phase Epitaxy

Abstract: The surface morphology and structure of AlN deposited by metal organic vapor phase epitaxy (MOVPE) on Si (111) at growth temperatures ranging from 825 to 1175°C was investigated. Transmission electron microscopy (TEM), reflection high energy electron diffraction (RHEED), atomic force microscopy (AFM), and secondary ion mass spectrometry (SIMS) techniques were used to study the resulting film structure. Growth at high temperatures but less than ~1100°C, resulted in a wire texture with some degree of in-plane al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…AFM studies of surface morphology in films of thickness greater than 200 nm thick showed that the AlN films grow by nucleation and coalescence of 3D islands. In agreement with earlier reports [5] the islands are equiaxed and faceted in films grown above 1000 C, anisotropic in films grown at 800 C and again equiaxed and non-faceted in films grown at 600 C. Grain size in the AlN films, as measured from the AFM scans, was found to increase with film thickness and temperature but changed very little with growth rate at a fixed temperature. As explained in the next section, the effect of grain size is expected to be less than the scatter in the data at a fixed temperature and masked by other effects that contribute to growth stresses with changes in temperature.…”
Section: Film Characteristicssupporting
confidence: 91%
See 1 more Smart Citation
“…AFM studies of surface morphology in films of thickness greater than 200 nm thick showed that the AlN films grow by nucleation and coalescence of 3D islands. In agreement with earlier reports [5] the islands are equiaxed and faceted in films grown above 1000 C, anisotropic in films grown at 800 C and again equiaxed and non-faceted in films grown at 600 C. Grain size in the AlN films, as measured from the AFM scans, was found to increase with film thickness and temperature but changed very little with growth rate at a fixed temperature. As explained in the next section, the effect of grain size is expected to be less than the scatter in the data at a fixed temperature and masked by other effects that contribute to growth stresses with changes in temperature.…”
Section: Film Characteristicssupporting
confidence: 91%
“…It has been shown that the tensile thermal stress on Si can be mitigated, to some extent, by changes in the composition and structure of the buffer layer [2][3][4]. However, in spite of the fact that buffer layers strongly impact the quality of the epilayers, there are very few studies [5] in the literature on the growth of the AlN buffer layer itself, other than to study its effect on the GaN epilayer. Data on growth stresses in nitrides are also scarce [2,3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GaN is not suitable for direct epitaxial growth on silicon substrates. Use of AlN as an intermediate buffer layer is one of the most promising ways to achieve high-quality GaN layers on Si and such AlN nucleation layers have been widely used during metalorganic chemical vapor deposition (MOCVD) and MBE growth [6][7][8][9][10]. Compared to Si, AlN has smaller lattice (2.4% vs. 19%)) and thermal expansion mismatch (+26% vs. 100%) with GaN.…”
Section: Introductionmentioning
confidence: 99%
“…In sample C the size of shalelike structure decreases and a large number of big pits appear, whose density was approximately 1.2 Â 10 8 cm À 2 . As known [15][16][17] AlN buffer layer grown on Si (1 1 1) is necessary and island nucleation is a typical mechanism in the AlN buffer layer growth, which can give rise to the c-component dislocation in GaN/AlN/Si (1 1 1) system [18][19][20][21]. In our sample's composite buffer layer, the AlN/Si (1 1 1) interface still exists.…”
Section: Resultsmentioning
confidence: 79%